2005
DOI: 10.1111/j.1067-1927.2005.130109.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of expression of transforming growth factor‐β and its receptors and their possible relationship with scarless healing in human fetal skin

Abstract: Fetal cutaneous wounds that occur in early gestation heal without scar formation. Although much work has been done to characterize the role of transforming growth factor-beta (TGF-beta) isoforms and their receptors in the wound healing process, their roles in scarless wound repair observed in early gestation and their functions in human fetal skin development, and structural and functional maintenance are still not well understood. In this study, we explore the expression and distribution characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 22 publications
5
81
0
2
Order By: Relevance
“…In line with observations of Chen et al [8], strong IHC staining for TGF-β1 was observed in the adult epidermis and dermis while positive staining was mainly observed in the fetal epidermis and the staining in fetal dermis was weak. TGF-β3 staining was observed in both the epidermis and dermis in fetal and adult skin but the staining was weaker in adult skin.…”
Section: Differential Ratios Of the Tgf-β Isoforms In Fetal And Adultsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with observations of Chen et al [8], strong IHC staining for TGF-β1 was observed in the adult epidermis and dermis while positive staining was mainly observed in the fetal epidermis and the staining in fetal dermis was weak. TGF-β3 staining was observed in both the epidermis and dermis in fetal and adult skin but the staining was weaker in adult skin.…”
Section: Differential Ratios Of the Tgf-β Isoforms In Fetal And Adultsupporting
confidence: 90%
“…In this study the differential gene expression for the TGF-β isoforms in fetal skin was confirmed with low mRNA expression for TGF-β1 and high expression for TGF-β2 and -β3 (table 2) [8,10,11]. In line with observations of Chen et al [8], strong IHC staining for TGF-β1 was observed in the adult epidermis and dermis while positive staining was mainly observed in the fetal epidermis and the staining in fetal dermis was weak.…”
Section: Differential Ratios Of the Tgf-β Isoforms In Fetal And Adultsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that GCs suppress the expression of TGF␤1 and -2 but do not affect TGF␤3. Scarless (fetal-like) wound healing is associated with a lack of TGF␤1 and -2 response during fetal wound healing, whereas TGF␤3 activity remains intact (53). Therefore, our results would indicate that GCs may contribute to the reduction of scar formation by suppressing the expression of TGF␤1 and TGF␤2 but not of TGF␤3.…”
Section: Of Gc-regulated Genesmentioning
confidence: 71%
“…Collagen production can be stimulated by the expression of TGF-β1 (38,39). However, immunohistochemical staining for TGF-β1 showed a decrease in this cytokine on days 7 and 14 in the presence of NLB, whereas an increase was observed in the ePTFE and sham groups.…”
Section: Discussionmentioning
confidence: 96%